AKTIVITAS ANTIBAKTERI KOMBINASI EKSTRAK DAUN NILAM (Pogostemon cablin Benth.) DAN DAUN KEMANGI (Ocimum basilicum L.) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - Rindengan, Elvie Rifke; Gurning, Sri Handayani; Paputungan, Marcelia; Ulaen, Selfie Petronela Joice; Maramis, Rilyn Novita (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Infections caused by Staphylococcus aureus bacteria can lead to various health problems, including skin infections that result in redness, swelling, blisters, and pus-filled lumps. The use of herbal plants is an alternative treatment for infections. Plants known to have antibacterial potential include patchouli leaves (Pogostemon cablin Benth.) and basil leaves (Ocimum basilicum L.). This study aims to determine the antibacterial activity of a combination of patchouli leaf extract (Pogostemon cablin Benth.) and basil leaves (Ocimum basilicum L.) against the growth of Staphylococcus aureus bacteria. The type of research used is a laboratory experiment. Extraction of patchouli leaves and basil leaves was performed using the maceration method with 96% ethanol. The test solution was prepared in three concentrations: 10%, 15%, and 20%. The combination was made by mixing each concentration in 1:1 ratio. The antibacterial activity test was conducted using the disc diffusion method, with a positive control consisting of erythromycin discs and a negative control of a 1% Tween 80 solution. Observations were made for 24 hours, then the inhibition zone around the paper disc was measured using a caliper. The combination of patchouli and basil leaf extracts can inhibit the growth of Staphylococcus aureus bacteria.